Review Study Evaluation Of Smart Indonesia Card Implementation Through Smart Indonesia Program - Ridwan, Ahmad; Afriadi, Bambang (PT. BATARI EDU CALYA, 2023)
This study evaluates several research results on the Smart Indonesia Card through the smart Indonesia program (PIP), how it is implemented and whether it takes place as expected or not. The method used in analyzing is this research is Mixed studies review / mixed methods review, which refers to any combination of methods where one important component is literature review. The data used in this study was obtained through literature studies by searching, collecting and reading various journals or articles about KIP (Smart Indonesia Card). After conducting a literature study and collecting data, then the data analysis process is carried out by referring to various references that have been used. The results of the research discussion show that the implementation of the Smart Indonesia Card policy in an effort to equalize education has run as it should, but in terms of its implementation in the field, there are still many shortcomings, as seen from indications that there are still many mistargets for students who should not be eligible to hold the Smart Indonesia Card (KIP)